English Learning Strategy in Islamic Boarding School - Rifiyanti, Hafizah; Hardianti, Hardianti; Nurhayati, Iis; Rahayu, Sri; Nurtika, Maola (BABASAL English Education Journal, 2024)
The purpose of this study is to investigate the integration of English language learning in the context of Islamic education at Pesantren Daaruttaqwa. The study uses a qualitative method with a focus on document analysis. The main data sources came from various related documents, such as school policies, learning materials, or related publications. The results of this study show that pesantren have successfully integrated English language learning with Islamic education through various means, including the use of Arabic for religious content and English for general subjects and being one of the languages of instruction and daily communication. This comprehensive approach ensures that students not only gain linguistic proficiency but also imbibe religious teachings, fostering a well-rounded educational experience.